2006
DOI: 10.1093/brain/awl093
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of spontaneous confabulations: a strategic retrieval account

Abstract: The 'temporality' hypothesis of confabulation posits that confabulations are true memories displaced in time, while the 'strategic retrieval' hypothesis suggests a general retrieval failure of which temporal confusion is a common symptom. Four confabulating patients with rupture of an anterior communicating artery (ACoA) aneurysm, eight non-confabulating ACoA controls and 16 normal controls participated in three experiments designed to test the two hypotheses. In Experiment 1, participants were tested on two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
267
5
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 262 publications
(296 citation statements)
references
References 40 publications
22
267
5
2
Order By: Relevance
“…Moreover, Gilboa et al (2006) obtained a similar pattern of results on a task in which participants were asked to make difficult, visuo-perceptual discriminations, instead of temporal context judgements. Gilboa et al (2006) concluded that, whilst TCC errors might be sensitive to confabulation, they were not specific to this condition.…”
Section: Accepted Manuscriptmentioning
confidence: 52%
See 4 more Smart Citations
“…Moreover, Gilboa et al (2006) obtained a similar pattern of results on a task in which participants were asked to make difficult, visuo-perceptual discriminations, instead of temporal context judgements. Gilboa et al (2006) concluded that, whilst TCC errors might be sensitive to confabulation, they were not specific to this condition.…”
Section: Accepted Manuscriptmentioning
confidence: 52%
“…On the other hand, Gilboa and Moscovitch (2002); (Gilboa et al, 2006); McVittie (McVittie, McKinlay, Della Sala, & MacPherson, 2014) have argued that there is overlap between these categories of confabulation or, at least, not a clear boundary between them (very florid confabulations can be, at least partially, 'provoked').…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations